PENGARUH POLITK HUKUM DALAM PENEGAKKAN HUKUM DI INDONESIA - Servasius Edwin Telaumbanua; Ismaidar, Tamaulina Br.Sembiring (ADISAM PUBLISHER, 2024)
This study examines the influence of legal politics on law enforcement in Indonesia, focusing on the interaction between politics and law in the formation and implementation of law. In the Indonesian context, politics often dominates the creation and implementation of law, leading to an imbalance between the values of justice and political interests. This study identifies three main questions: how politics influences the formation and implementation of law, factors that influence the effectiveness of law enforcement, and the extent to which political intervention affects the independence of law enforcement agencies. Using a qualitative literature study method, this study analyzes relevant literature to understand the impact of politics on the Indonesian legal system. The results show that political intervention influences the formation of law, the substance of law, and law enforcement which is not always fair. This study recommends the need for a balance between politics and law, as well as strengthening the independence of law enforcement agencies in order to create a fair and transparent legal system